Evaluasi Program Bimbingan dan Konseling Dengan Model CIPP - Agista, Nurtazkiyah; Irawan, Sapto; Agustin, Adhi Krisna Maria (Universitas Kristen Satya Wacana, 2025)
This study aims to evaluate the implementation of the guidance and counseling program at SMPN 4 Salatiga. Guidance and counseling services are one of the school's efforts to support students in dealing with problems and developing their maximum potential. The evaluation model used is the CIPP (Context, Input, Process, and Product) evaluation model to obtain a comprehensive and in-depth picture of the guidance and counseling program at SMPN 4 Salatiga. This research uses a qualitative approach with a descriptive method. Data were obtained from the deputy principal for curriculum, guidance and counseling coordinator, guidance and counseling teachers, and students of SMPN 4 Salatiga by using interview techniques and documentation studies. The results showed that some things have been implemented by the plan but some things have not been implemented. The Context aspect in making the vision and mission is by the vision and mission of the school and the program is made according to the needs of students. Input aspect, there is a standard match of counseling teachers by their educational background, although there is still one teacher who has not implemented PPG-BK. Process aspect, the counseling service has been running well, although only one class hour a week. Product aspect, the counseling program has tried to produce changes in students even though it is by each person.